Os tratados internacionais de direitos humanos como parâmetros para o controle da constitucionalidade das leis - Figueiredo, Patrícia Cobianchi (2009)
This work aims the recognition of international human rights treaties as parameters to the control of constitutionality under the perspective of the current stage of the Constitutional Right, which interacts with the International Human Rights Law. The primary responsibility as to the protection of human rights belongs to the States, which, in favor of these rights and of human dignity, should seek for means to improve the protection in the internal sphere. The international human rights treaties freely ratified by the States, besides supporting normatively the international system of protection, are committed to adequating the internal law with the international principles. In Brazil, following other States, the rights deriving from these tools when incorporated to the internal order are received by the Constitution, integrating it beyond its text. The Constitution itself determines this way of being, and there is no impediment in its rigidity since, besides the formality of elaboration process of international human rights treaties, protecting them from being modified by the legislator, the introduction of these tools in our order does not intend to modify the constitutional text. The rights resultant from the international treaties cause positive impact in the internal law order and should be considered in the interpretation of Constitution since they reaffirm and reinforce its principles. Therefore, they are parameters for the control of constitutionality. In the case of eventual conflict it should prevail the most favorable law, whether it is part of the Constitution or part of the international treaties. Finally, it is correct to say that the international human rights treaties as parameters for the control of constitutionality are fully welcomed in the existing systematics